Analysis of data and real time traffic model - Popovskaya, K. O. (Проблеми телекомунікацій, 2012)
In the article the experimental study of a multi-service network is carried out. In the assumption of a Poisson entrance flow of demands likelihood characteristics of multiservice system are received by transfer of real time traffic and traffic of data. These characteristics allow forming indicators of service quality of various services. Dependence of average of the macro packages being in turn, on intensity of an arriving traffic of data is received at its aspiration to limiting value. At aspiration λg to limiting value the average of macro packages in turn sharply increases. At the same time serving system passes to an unstable, critical mode. Dependence of probability of the lost macro packages on the size of the buffer and on pulse nature of receipt of macro packages is investigated. Results show that pulse nature of receipt of macro packages leads to considerable growth of losses in comparison with the smoothed traffic. At the same time, buffer existence damp pulse character of traffic and leads to reduction of losses. Researches of transmission quality of multiservice flows with use of machine experiment and the ns-2 program are carried out. The given results allow knowing about cross impact of different services flows, and their difficult character speaks features of the used technologies. Obviously, the greatest influence renders increase of real time flows. Results of the carried-out machine experiment allow choosing correctly loading of routers and can be used at design and balancing of network.
Keywords: multiservice network; router; NS2; QoS; priority; loss and delay of packages